Paternal peripartum depression and its risk factors among men transitioning into fatherhood in Malaysia - Yusuf, Mohamad Ya’akob; Ariffin, Farnaza; Ismail, Zaliha; Razali, Salmi (Faculty of Medicine, 2026)
Fatherhood can be challenging, and men’s well- being during their partner’s perinatal period is often overlooked. This study aims to assess the prevalence of paternal perinatal depression (PPND) and associated factors among men in a Malaysian district during their partner’s perinatal period. Methods: This cross-sectional study used a self-administered questionnaire for men whose partners attended the maternal and child health clinic (MCHC) during the perinatal period. Eligible participants received either a hard copy or a link to an online Google Form. The questionnaire covered sociodemographic, economic, and clinical details, as well as the Multidimensional Scale of Perceived Social Support (MSPSS) and the Edinburgh Postnatal Depression Scale (EPDS). Informed consent was obtained, and men with EPDS scores of 10 or higher were considered at risk for post-partum neural depression (PPND). Data were analyzed using SPSS version 26. Results: 400 men responded, but only 381 completed data were analyzed. The mean age of participants was 32.72 (±5.648). The prevalence of PPND in this sample was 12.4%. The two significant factors for PPND were low or moderate social support and the presence of existing chronic disease. Conclusion: The study concluded that men lacking social support are at an increased risk of PPND. It also emphasized that men with pre-existing chronic conditions face a higher risk of PPND. Therefore, it is crucial to screen for PPND in men, particularly those with chronic illnesses and limited social support. Additionally, the well-being of fathers should be considered in the follow-up and care of their female partners during the perinatal period.